Drones and the law : international responses to rapid drone proliferation - Sehrawat, Vivek (Emerald Publishing Limited, 2021)
"Combining expert insights into strategy, international law, international humanitarian law, targeted killing, ethics, and privacy, Vivek Sehrawat offers an important historical and context for understanding how drone usage has become widespread; investigates how international law and international humanitarian law on the use of force interact with the rapid proliferation of military drones; and outlines how civilian use of drones poses specific challenges to national privacy laws in large countries such as the UK, the USA, and India. Throughout, Sehrawat discusses potential world policies for drone strikes and counter terrorism and debunks myths about current drone capabilities and the law regarding drone usage, making this book a useful and timely addition to the growing literature on drones and the law"--